(3GdeYJeO aj CUhd Gdabgs - (3CHh GdbGSe Hf CMeO Hf Ydj Hf EHQGgje GdRjGfj , J (B1249 (3g`s
(3ChdgG (B:s
(3Efg dh LGR Cf jchf YedfG HeG GNHQfG Hg Yf GdfHi Ydjg GdSdGe s
(3BNQgG (B:s
(3ef RcGg GdeRci agh ZQVfG hdjS SHH gPG GdXf gPg GdeTbI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1732s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3CUhd (B81) s
Keywords: (3CUhd Gdabgs